Effect of Number of Electrodes on Electrical Performance of Surface Dielectric Barrier Discharge Plasma Actuator - Andrew Ragai, Henry Rigit; Imran, Ali; Tiaw, C Boon; Chi, Hung Chong (2020)
Dielectric barrier discharge (DBD) represent their wide application in controlling aerodynamic flow by plasma actuators. Their effectiveness is affected by the shape, type size, and thickness of electrodes. This paper investigates the influence of the number of electrodes on the electrical functioning of surface DBD plasma actuator. For this purpose, five different configurations of plasma actuator with varying electrodes number from 4 to 8 are tested. The gap between the electrodes and the length and width of each electrode remains constant in all these configurations. It was found that on increasing the number of electrodes and the applied frequency (1 kHz to 5 kHz) the value of maximum withstand voltage was decreased. However, the discharge power was increasing slightly on increasing the number of electrodes. This slight change in discharge power resulted in the significant plasma formation on the surface of the plasma actuator, the effect was visually captured by a CCD camera.